DEVELOPING LINGUISTIC COMPETENCE OF B1 LEVEL LANGUAGE LEARNERS IN THE ONLINE EDUCATIONAL ENVIRONMENT - Ruziyeva, Mukhlisa (MMIT Proceedings, 2023)
Online courses are a new way of learning anywhere you go. The new software’s are making it easy to use for anyone who might not be familiar with the technology. Sitting in a traditional classroom for hours and hours compared to being able to study anywhere in the world. Leaving behind the traditional heavy books that we have to carry around the whole day, now all we need is our electronic devices. Although online course was accepted by a lot of people, I was not ready to leave the traditional classroom. The fear of managing and organize my own time for the online classes held be back because when managing time is in my hands, I am able to work at my own pace and whenever I like. After examining several conceptual elements of linguistic competence of B1 level language learners through online educational environment, this article presents a study analyzing the effects of online teaching in the linguistic competence of B1 level language learners. The results, students' linguistic competence could be improved in the online educational environment with the help of variety of specific methods.